As implicações dos indicadores de desempenho contratualizados na prática clínica da Medicina Geral e Familiar: um modelo profissional em mutação? - Raposo, Hélder (Sociologia: Revista da Faculdade de Letras da Universidade do Porto, 2018)
Considering the organizational innovations introduced by the reform of the Primary Health Care in Portugal, we intend to analyze the implications of the contractualisation of performance indicators in the clinical work of General Practice and in the foundations of its professional model. Based on a case study developed in two different organizational contexts, it was possible to verify the emergence of some perverse effects of managerialism in the professional world of this medical specialty, such as an increased volume of more bureaucratic workload, a restrictive evaluation of professional performance or the constraints to develop a patient-centered medicine.